Is that lumbar disc symptomatic? Herniated lumbar disc associated with contralateral radiculopathy - Abdul Jalil, Muhammad Fahmi (BMJ Publishing Group, 2014)
Herniated lumbar disc may be asymptomatic or associated with lower limb radiculopathy. Most spinal surgeons would offer surgery following a period of conservative measures if the radiological and clinical findings correlate. However, the existing dictum that lumbar radiculopathy should correlate with ipsilateral lumbar disc herniation may not be accurate as it can rarely present with contralateral sciatica. Literature regarding this phenomenon is scarce. Therefore, we report a patient with herniated lumbar disc presenting with predominantly contralateral motor weakness radiculopathy, which resolved after discectomy.